Chrysanthemum, Edible—Chrysanthemum coronarium L. - James M. Stephens (EDIS, 2003)
This document provides an overview of the edible chrysanthemum, also known as garland chrysanthemum. Commonly consumed in the Orient, it is recognized for its whitish green, notched leaves. The plant thrives in Florida gardens when seeds are sown in fall or spring, with winter production possible in South Florida. Standard vegetable gardening practices are recommended. The young leaves are ready for harvest about a month after sowing, and the flowers are bright yellow and daisy-like. Original publication date May 1994.